Training in Mathematics Education from a Sustainability Perspective: A Case Study of University Teachers' Views - Francisco Manuel Moreno-Pino; Rocío Jiménez-Fontana; José María Cardeñoso Domingo; Pilar Azcárate Goded (MDPI AG, 2022)
Humankind is faced with major global challenges to ensure the future of our planet. Target 4.7 of Sustainable Development Goal 4 (quality education) of the 2030 Agenda establishes the importance of ensuring that all learners acquire the theoretical and practical knowledge needed to promote sustainable development through education for sustainable development, human rights, gender equality, and global citizenship, amongst others. The research presented in this article is based on an exploratory study on the views of a group of university teachers from the area of Didactics of Mathematics in the Faculty of Education Sciences at Universidad de Cádiz with regard to Education for Sustainability and its integration in the field of training future teachers in mathematics education. It aims to analyse the perceptions teachers have regarding the subject of study, the work methodologies they use, etc. in greater depth. The authors of the research later interviewed three teachers in the area of Didactics of Mathematics who teach in different education degrees: bachelor's degree in early childhood education, bachelor's degree in primary education, and master's degree in teacher training for compulsory secondary education and baccalaureate. Three instruments were used to collect data: the syllabi of the subjects for which the teachers were responsible, an initial exploratory questionnaire, and a semi-structured personal interview. The instrument employed to analyse the information was the Tool for Methodological Analysis through Sustainability (Herramienta de Análisis Metodológico desde la Sostenibilidad, HAMS in Spanish). The results show the different views and positions the university teachers in the area of Didactics of Mathematics at Universidad de Cádiz have with respect to integrating sustainability into future teachers' training in mathematics education. It is concluded that the effective integration of sustainability into mathematics education requires university teachers to change and to work together from the same perspective-the one they intend to promote.